Technology Entrepreneurship Project (ENT 600) : Panasonic Sdn. Bhd. / Zawani Ab Wahab - Ab Wahab, Zawani (2021)
This case study assignment was designed to learn how the company managed to design, produce, and markets their products. The company that I had chosen is Panasonic Sdn Bhd, it is because this company has been in long time in business sector. I had chosen the stand fan that has been produced by this company which is Stand Fan (16’’) MT405. Fan is a cooling appliance including the air conditioner, but the air–condition has a higher power consumption. So, this case study is to analysis about the fan and improvised some problems that can reduce the quality of the product. Although this model has some strengths such as the shape and the number was suitable to increase the airflow, it also has height-adjustable, the cover of the fan was made up from metal which can make it last longer and lastly it has the timer mode to let the fan operate. There were some problems obtained from this fan. First, when discussing about the stand fan, the main component that must be examine is the material of the blades, it must have a long-time life span in order to use for a long time. Moreover, this fan also must have smart features such as sensors and also microcontroller to adjust the level of speeds and also to control the switch system. This will make the users more satisfied with this product. Other than that, this fan also must add the solar panels as the other source of energy since the old fan from Panasonic only use the electrical energy, which can lead to high electrical bill. Thus, after all the improvements been applied, I sure that this fan will have a better quality and has high sale in market. The name of this fan is Smart Solar Fan, which showed that this fan has a smart features and needs the solar energy.